Impact of multi-limb oscillometric cuff measurements on hemodynamics: insights from pulse wave propagation modeling - Wolos, Kamil; Pstras, Leszek; Debowska, Malgorzata; Poleszczuk, Jan (Frontiers in Physiology, 2025)
ObjectiveMulti-limb oscillometric cuff measurements can be used for estimating various vascular parameters and evaluating side differences in arterial pulse waveforms. In this study, we conduct an in silico investigation to evaluate the potential impact of such measurements on hemodynamics.MethodsWe employed a 0–1D model of pulse wave propagation to examine the relationship between different levels of oscillometric cuff pressure applied simultaneously at multiple sites (right above the wrists and/or ankles) and the resulting changes in blood pressure and flow at selected sites in the vascular system, assuming the absence of cardiovascular regulatory mechanisms. The simulations included various combinations of cuff placements, including four cuffs applied simultaneously on all limbs. In addition, we conducted both global and local sensitivity analysis to evaluate the impact of selected cardiovascular parameters on the simulation results.ResultsIn the case of cuffs placed on all four limbs and inflated to suprasystolic pressure - effectively occluding the vessels beneath the cuffs - our simulations indicated an increase in mean arterial pressure (MAP) of approximately 10% in the ascending aorta, left common carotid artery, and abdominal aorta. Additionally, the mean carotid artery blood flow increased by approximately 11% compared to baseline value. In contrast, for the case with a cuff placed only on one wrist, we observed a significantly smaller MAP increase of only 2.5%, with a 3% rise in mean carotid artery flow. Our sensitivity analysis revealed that these changes can be mitigated by relatively small adjustments in specific cardiovascular parameters, suggesting that properly functioning physiological regulatory mechanisms should easily compensate for the cuff induced hemodynamic alterations. Furthermore, global sensitivity analysis demonstrated that relatively similar increases in MAP and mean carotid blood flow are expected for different combinations of cardiovascular parameters values, indicating the robustness of our findings.SignificanceThis in silico study suggests that multi-limb cuff-based measurements may induce measurable central hemodynamic alterations if not counteracted by cardiovascular regulatory mechanisms. This suggests that such measurements may not be innocuous to individuals with some deficiencies in cardiovascular regulation. Further investigation is warranted to verify this in vivo and, if necessary, establish appropriate safety protocols.